IDENTIFIKASI AIR TANAH MENGGUNAKAN METODE GEOLISTRIK DI KECAMATAN POMALAA KABUPATEN KOLAKA PROPINSI SULAWESI TENGGARA - Sudarwin Kamur (UNIVERSITAS NEGERI MAKASSAR, 2022)
ABSTRACTThis research is motivated by development and population growth continues to increase from day to day. The impact of population growth is the increase in residential land. The increase in residential land is sometimes not accompanied by the provision of clean water by PDAM, so that people use dug wells or drilled wells. In the Kolaka area, especially the Kolaka District area, which is the research location, it is also a location that is difficult to find fresh water, so the geoelectric method plays a very important role in efforts to determine which locations contain fresh water. This research uses resistivity geoelectric method with Wenner and Schlumberger configuration. Processing data using Res2Dinv to map 2D isoresistivity. The well depth data was processed using Microsoft Excel, Surfer 10.2 application and ArcGIS to create a groundwater network map. The measurement trajectory uses a space of 7 meters, 20 meters and 40 meters. The results of the study obtained different resistivity values for each rock. The resistivity variation obtained starts from 0.453 – 13,988 m. Groundwater resistivity values are in the range of resistivity values of 0.453 – 33.3 m. The lithology of the aquifers in the study area is alluvial and sandstone. In the research location, groundwater is generally found at a depth of more than 5 meters